PENINGKATAN KUANTITAS DAN KUALITAS USAHA KOPI BUBUK DI DESA PERMU KECAMATAN KEPAHIANG KABUPATEN KEPAHIANG - Alnopri -; Prasetyo Prasetyo; Yessi Rosalina (Universitas Bengkulu, 2018)
Community service activities have been carried out in the Permu Village, Kepahiang Subdistrict, Kepahiang District. The target group is the group of mothers who take shelter Permu village in the